Informed Consent, Anticipatory Regulation and Ethnographic Practice - Murphy, Elizabeth; Dingwall, Robert (Elsevier, 2007)
In this paper we examine the application of informed consent to ethnographic research in health care settings. We do not quarrel with either the principle of informed consent or its translation into the requirement that research should only be carried out with consenting participants. However, we do challenge the identification of informed consent with the particular set of bureaucratic practices of ethical review which currently operate in Canada, the US and elsewhere. We argue that these anticipatory regulatory regimes threaten the significant contribution of ethnographic research to the creation of more efficient, more effective, more equitable and more humane health care systems. Informed consent in ethnographic research is neither achievable nor demonstrable in the terms set by anticipatory regulatory regimes that take clinical research or biomedical experimentation as their paradigm cases. This is because of differences in the practices of ethnographic and biomedical research which we discuss. These include the extended periods of time ethnographers spend in the research setting, the emergent nature of ethnographic research focus and design , the nature and positioning of risk in ethnographic research, the power relationships between researchers and participants, and the public and semi-public nature of the settings normally studied . Anticipatory regulatory regimes are inimical to ethnographic research and risk undermining the contribution of systematic inquiry to understanding whether institutions do what they claim to do, fairly and civilly and with an appropriate mobilisation of resources. We do not suggest that we should simply ignore ethics or leave matters to the individual consciences of researchers. Rather, we need to develop and strengthen professional models of regulation which emphasise education, training and mutual accountability. We conclude the paper with a number of suggestions about how such professional models might be implemented.